Dampak Pariwisata Terhadap Usaha Mikro Kecil Menengah di Desa Perkebunan Bukit Lawang - Siregar, Fadlan Ramadhan; Dalimunthe, Femmy Indriany; Sibuea, Livia Ester L; Sidabutar, Melvina Hotma Uli (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2024)
Tourism has a huge impact on economic growth, one of which is in reducing unemployment and increasing the productivity of a region, not only that the tourism sector also has a considerable impact on local MSMEs in the area. Bukit Lawang Plantation Village is one of the tourist areas whose local MSMEs depend on the tourism sector and rely on tourists as their main income. This study aims to analyse the impact of tourism on local MSMEs in Bukit Lawang Plantation Village using the PEST analysis framework which includes four main factors, namely political factors, economic factors, social factors and technological factors. The method used in this research is qualitative research method, this research uses interview techniques in collecting data, the informants interviewed are the owners of local MSMEs in Bukit Lawang Plantation Village. From the results of the research conducted, the factor that gets the biggest impact of tourism is the economic factor because tourism has a big influence in becoming the main income of local MSME owners.